High Risk Molar Pregnancy Treated by Chemotherapy and Surgery: A Case Report - Carbone, Fabiana; Santangelo, Giusi; Scudo, Maria; Fracassi, Alice; Gentile, Gabriella; Donato, Violante Di; Palaia, Innocenza; Spiniello, Lorenzo; Perniola, Giorgia (Archives of Clinical and Medical Case Reports, 2022)
Background: Gestational trophoblastic disease (GTD) is a rare developmental form of proliferative trophoblastic tissue. Scarse literature exists regarding the optimal management of patients with advanced GTD. We report a case of high risk GTD treated with poly-chemotherapy prior to uterine suction curettage. Case: A 29-year-old woman presented high risk GTD. She was treated with three cycles of poly-chemotherapy in another hospital and then she was referred to our emergency room for the surgical management. Conclusion: This case highlights the possibility of conservative treatment of GTD.